IL-1β and IL-6 Are Highly Expressed in RF+IgE+ Systemic Lupus Erythematous Subtype - Yongkang Wu; Bei Cai; Junlong Zhang; Beilei Shen; Zhuochun Huang; Chunyu Tan; Carla C. Baan; Lanlan Wang (Journal of Immunology Research)
Background. Systemic lupus erythematosus (SLE) is an autoimmune disease with great heterogeneity in pathogenesis and clinical symptoms. Rheumatoid factor (RF) is one key indicator for rheumatoid arthritis (RA) while immunoglobulin E (IgE) is associated with type I hypersensitivity. To better categorize SLE subtypes, we determined the dominant cytokines based on familial SLE patients. Methods. RF, IgE, and multiple cytokines (i.e., IL-1β, IL-6, IL-8, IL-10, IL-17, IFN-γ, IP-10, MCP-1, and MIP-1β) were measured in sera of familial SLE patients (n=3), noninherited SLE patients (n=108), and healthy controls (n=80). Results. Three familial SLE patients and 5 noninherited SLE cases are with features of RF+IgE+. These RF+IgE+ SLE patients expressed significantly higher levels of IL-1β and IL-6 than the other SLE patients (P<0.05). IL-6 correlated with both IgE and IL-1β levels in RF+IgE+ SLE patients (r2=0.583, P=0.027; r2=0.847, P=0.001), and IgE also correlated with IL-1β (r2=0.567, P=0.031). Conclusion. Both IL-1β and IL-6 are highly expressed cytokines in RF+IgE+ SLE subtype which may be related to the pathogenesis of this special SLE subtype and provide accurate treatment strategy by neutralizing IL-1β and IL-6.